COMPARISON BETWEEN THERAPEUTIC ULTRASOUND AND SCAR MOBILIZATION OVER PERSISTENT POSTNATAL DYSPAREUNIA - Sf, Mariyam Farzana; P, Ponmathi; Pvr, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Dyspareunia is known as the painful sexual intercourse. This study was conducted to compare the effectiveness between therapeutic ultrasound and scar mobilization in persistent postnatal dyspareunia. Methods: This is an experimental study. 30 subjects with superficial dyspareunia, age group between 25 and 35 years are taken in this study and 15 subjects in Group A were treated with ultrasound therapy, 15 subjects in Group B were treated with scar mobilization. Female sexual functional index questionnaire (FSFI) and visual analogue scale (VAS) were used as the outcome measure. Results: Results showed a significant difference in FSFI and VAS measurements in both the groups, but clinically Group A showed better improvement in pain and quality of life than Group B. Conclusion: There is no significant difference between ultrasound therapy and scar mobilization over the pain and quality of life in patients with persistent postnatal dyspareunia.